2016
DOI: 10.4236/health.2016.815163
|View full text |Cite
|
Sign up to set email alerts
|

Serum 1, 25-Hydroxyvitamin D: A Useful Index of Cognitive and Physical Functional Impairment in Healthy Older Adults in Japan: A Pilot Study

Abstract: We enrolled 23 Japanese men (age: 76.0 ± 8.7) and 17 women (age: 78.3 ± 9.3) in this study. The physical function of even a person getting on a wheelchair could be tested in all subjects. Blood was collected by venipuncture and the serum 1, 25-hydroxy vitamin D (1, 25OHD) concentration was measured. The Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment-Japanese version (MoCA-J) was used for the cognitive function test. Physical function was measured objectively using the Timed UP and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Vitamin D3 supplementation improves muscle function and physical performance in the elderly population using 4 meter gait speed test (4 MGS) [11]. In our latest study, a significant positive correlation was found between urinary 25 OHD/creatinine and MMSE or Japanese version of the MoCA (MoCA-J), and a significant negative correlation between serum 1,25 OHD and TUG or 4 MGS [12]. Other studies, however, have not found an association between vitamin D and physical performance [13] [14] [15] [16] [17].…”
Section: Introductionmentioning
confidence: 79%
“…Vitamin D3 supplementation improves muscle function and physical performance in the elderly population using 4 meter gait speed test (4 MGS) [11]. In our latest study, a significant positive correlation was found between urinary 25 OHD/creatinine and MMSE or Japanese version of the MoCA (MoCA-J), and a significant negative correlation between serum 1,25 OHD and TUG or 4 MGS [12]. Other studies, however, have not found an association between vitamin D and physical performance [13] [14] [15] [16] [17].…”
Section: Introductionmentioning
confidence: 79%
“…En lo referente a los niveles de vitamina D y su relación con las caídas, aunque no se encontró significancia estadística, es pertinente destacar que esta vitamina contribuye a mejorar la función física como lo expresaron en su estudio Hasegawa et al 27 . De igual manera, Bischoff-Ferrari et al 28 afirmaron que un nivel adecuado de vitamina D se asocia con una mejoría en la función muscular que conlleva a disminuir el riesgo de caídas, unido al efecto protector sobre las fracturas por el beneficio de la vitamina D en la homeostasis del calcio, asimismo, Bischoff-Ferrari, et al 29 destacaron que la debilidad muscular proximal es una característica clínica importante de la deficiencia de vitamina D y los niveles de 25OHD se asocian con la función de las extremidades inferiores, mejorando progresivamente hasta 40 ng/ml.…”
Section: Discussionunclassified
“…Vitamin D supplementation caused significant improvement in cognitive performance assessed by MMSE score in Alzheimer's disease [12][13][14]. In our latest study, a significant positive correlation was found between urinary 25-hydroxy vitamin D (25OHD)/creatinine and MMSE or the Montreal Cognitive Assessment-Japanese version the Montreal Cognitive Assessment-Japanese version (MoCA-J) [15].…”
mentioning
confidence: 99%